2019
DOI: 10.3390/molecules24132351
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Profiling, Quantitative Assessment and Biological Activities of Tunisian Native Mentha rotundifolia (L.) Huds.

Abstract: Phenolic profiling of ten plant samples of Mentha rotundifolia (L.) Huds. collected from different bioclimatic areas of Tunisia, was for the first time carried out by using a fast ultra-high-performance liquid chromatography (UHPLC)-high resolution tandem mass spectrometry (HRMS/MS) method on a Q Exactive platform equipped with an electrospray ionization (ESI) source. An intraspecific, interpopulation variability was evidenced and a total of 17 polyphenolic metabolites were identified and quantified by using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In addition to caffeic acid (peak 3) and rosmarinic acid (peak 21) this research has shown the presence of ten other caffeic acid esters (peaks 1,7,15,19,22,24,25,27,30,34) known as lithospermic acids or salvianolic acids. Caffeic acid, rosmarinic acid, lithospermic acid A (peak 22), and lithospermic acid B (peak 24) were identified using authentic standards or herbal reference materials (Salvia miltiorrhiza Bunge, Melissa officinalis L.) and literature data [32,34,35]. Interpretation of data from MS/MS experiments for remaining peppermint caffeetannins is presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to caffeic acid (peak 3) and rosmarinic acid (peak 21) this research has shown the presence of ten other caffeic acid esters (peaks 1,7,15,19,22,24,25,27,30,34) known as lithospermic acids or salvianolic acids. Caffeic acid, rosmarinic acid, lithospermic acid A (peak 22), and lithospermic acid B (peak 24) were identified using authentic standards or herbal reference materials (Salvia miltiorrhiza Bunge, Melissa officinalis L.) and literature data [32,34,35]. Interpretation of data from MS/MS experiments for remaining peppermint caffeetannins is presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Flavanones (peaks 6, 8, 11, 13, 16, 29, 32, 35) were detected on the U(H)PLC chromatograms between 11.13 and 16.35 min. Six peaks (6, 13,16,29,32,35) were identified as eriocitrin, narirutin, hesperidin, eriodictyol, naringenin, and hesperetin, respectively. Their fragmentation, t R and UV-Vis spectra corresponded to proper parameters of authentic standards and literature data [38].…”
Section: Resultsmentioning
confidence: 99%
“…Mint species have also been used for medicinal aims, such as in infusions or tinctures for the treatment of intestinal colic, liver disorders, gastritis, and jaundice, as well as for headaches and migraine [ 6 ]. Mint extracts were found to contain a wealth of compounds, collectively named terpenoids and polyphenols, which include phenolic acids, flavones, and flavanols, in their free forms or as glycoconjugates [ 7 ]. Similar components were also found in the leaves and flowers of small wild plants growing in Saudi Arabia named Lantana camara , Anvillea garcinii , and Strychnos nux-vomica [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols have been found to possess high antioxidant activity as well as a plethora of favourable benefits to human health (Queen and Tollefsbol 2010 ; Ben Haj Yahia et al. 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…From our result, BPFRF, quercetin, and ascorbic acid caused a concentration-dependent increase in the inhibition of the DPPH radical Figure 4. DPPH is a stable nitrogen-based free radical that functions as a substrate of radical-trapping reactions in this method (Assefa et al 2016;Ben Haj Yahia et al 2019). The BPFRF caused a fast conversion of the purple-colored DPPH radical to pale yellow.…”
Section: Identification and Characterization Of Bpfrf By Uplc-esi-qtof-msmentioning
confidence: 99%